The Dynamics of the Social History of Islamic Law from the Classical Period to the Caliphate - Amaranti, Emira; Ara, Fatimah Jihan; Razi, Fahrur (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This article aims to examine the dynamics of the development of Islamic law from the time of the Prophet Muhammad (PBUH) to the Abbasid Dynasty from the perspective of social history. This research uses a qualitative-descriptive approach and historical method, by examining the sources of classical and contemporary literature. The results of the study show that Islamic law has been shaped by the interaction between divine revelation and the social reality of society. The process of law formation during the time of the Prophet was greatly influenced by the social context of Arab society, while during the period of Khulafaur Rashidin to Abbastial, Islamic law underwent institutionalization, codification, and development of legal methodology (ushul fiqh). This study confirms that Islamic law is dynamic and adaptive to social change, making it relevant to answer the challenges of modernity.